Selective Attention Measurement of Experienced Simultaneous Interpreters Using EEG Phase-Locked Response - Yagura, Haruko; Tanaka, Hiroki; Kinoshita, Taiki; Watanabe, Hiroki; Motomura, Shunnosuke; Sudoh, Katsuhito; Nakamura, Satoshi (Frontiers in Human Neuroscience, 2021)
We quantified EEG signals associated with the selective attention processing of experienced simultaneous interpreters using phase-lock responses induced from a 40-Hz-ASSR, which is robust to environmental changes. We divided our participants into two groups based on simultaneous interpretation experience: S-rank (n = 7) with over 15 years and C-rank (n = 15) with less than 1 year. We extracted the phase-locked responses induced by the 40-Hz-ASSR signals and calculated the value of the inter-trial coherence (ITC) and compared the simultaneous interpretation (SI) and shadowing (SH) conditions. On the anterior electrodes, the ITC value of the S-rank on the SI condition was significantly higher than the value of the SH condition, and no significant difference was detected on the C-rank between the conditions. Since the difference between SI and SH reflects the attention processing related to multiple language control of SI, we argue that the 40-Hz-ASSR method adequately verifies the continuous change of the selective attention processing of SI under real environments.